Program Makan Bergizi (MBG) Sebagai Katalis Peningkatan Kualitas Pembelajaran Di Sekolah Dasar - Erwin Eka Saputra (FKIP UNSULTRA, 2025)
The Nutritious Meal Program (MBG) is a strategic initiative that plays a crucial role in improving the quality of learning in elementary schools by meeting children's nutritional needs. This study aims to examine the relationship between the implementation of the nutritious meal program and improvements in concentration, attendance, and learning outcomes for elementary school students. The method used was a literature review, analyzing relevant national and international research findings from 2018–2024. The study results indicate that a balanced nutritional intake, particularly during breakfast and lunch at school, directly contributes to students' cognitive abilities, concentration, and active participation in the learning process. The MBG program impacts not only physical aspects such as children's growth and fitness, but also psychological and social aspects, such as increased learning motivation and a sense of community within the school environment. Thus, the MBG can serve as a catalyst for building a healthy, productive, and sustainable learning ecosystem. This study recommends synergy between schools, parents, and health institutions to strengthen the implementation of the nutritious meal program as an integral part of basic education policy in Indonesia.